FULFILLMENT OF INDICATORS AND ENHANCEMENT EXTRINSIC MOTIVATION OF STUDENTS THROUGH TEAMS GAMES TOURNAMENT IN GEOGRAPHY LEARNING - Sukron Operma; Ratna Wilis; Fitri Yanti Anas (Universitas Sebelas Maret (UNS), 2024)
The success of the learning process is the core goal of education. The success of the learning process can be seen from several things, one of which is student learning motivation. Learning motivation plays an important role in achieving learning success, and it has the potential to affect learning interest, activeness, and learning outcomes. The existence of strong learning motivation will catapult students to success in learning. Students' low motivation to learn is a concern for researchers to solve. This study aims to increase student motivation through learning team games tournament (TGT). The research method used in this study is Classroom Action Research (PTK) with a quantitative-descriptive approach. The data collection technique used is to distribute questionnaires that will be filled out by students. This research was conducted at SMAN 3 Padang on geography subjects. The results of this study show that teams games tournament (TGT) can meet extrinsic learning motivation indicators. The level of fulfillment of all indicators is more than 60% and even reached 72%, such a percentage is classified as